2016
DOI: 10.3928/01477447-20160414-02
|View full text |Cite
|
Sign up to set email alerts
|

Avulsion Fracture of the Tibial Tubercle Associated With Patellar Tendon Avulsion

Abstract: Avulsion fractures of the tibial tubercle in adolescent athletes are uncommon injuries, believed to be a result of forceful extension of the knee against a fixed leg. Concomitant injury to the ipsilateral patella tendon is even more rare, with few cases reported in the literature. The mechanisms responsible for this association are not well understood. The significance of this double insult to the knee extensor mechanism is the potential deleterious effect of misdiagnosis and/or mismanagement. In this case rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“… 8 Seo et al 9 reported that this same treatment was used successfully in a 14-year-old patient. The present results were similar to those of previously published studies 9 , 10 , 11 on this injury; 12 months after the injury, the patient was able to return to the sports activities without subjective symptoms or weakness of the extensor mechanism.…”
Section: Discussionsupporting
confidence: 92%
“… 8 Seo et al 9 reported that this same treatment was used successfully in a 14-year-old patient. The present results were similar to those of previously published studies 9 , 10 , 11 on this injury; 12 months after the injury, the patient was able to return to the sports activities without subjective symptoms or weakness of the extensor mechanism.…”
Section: Discussionsupporting
confidence: 92%
“…Mosier and Stanitski observed this type of fracture in 2 cases of tibial tubercle avulsion fractures in a study reviewing 19 of these fractures in 18 patients [ 1 ]. Many of the documented cases of these bipolar fractures occur in association with a jump, as seen with our patients, with basketball or track as two of the most commonly associated sports [ 3 5 ]. Our two cases are consistent with the jumping mechanism, and provide two examples of operative management of these injuries ( Table 1 ).…”
Section: Discussionmentioning
confidence: 91%
“…Limited range of motion due to pain or effusion from the avulsed tubercle can cause the variation in reported incidence. The presence of a palpable defect between the inferior pole of the patella and tibial tuberosity should heighten clinical suspicion for associated patellar tendon rupture [ 7 ]. If physical examination cannot be performed due to cast immobilization or pain, the presence of patella alta on radiographic imaging as well as calcified fragments below the patella may indicate the presence of patellar tendon rupture [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tibial tubercle avulsion fractures are managed operatively in most cases, and long-term outcomes are favorable with the resumption of sport to the previous level [ 4 ]. The high energy nature of the athletic injury is associated with compartment syndrome from bleeding into the anterior compartment, vascular injury [ 6 ], patellar tendon avulsion [ 7 ], and meniscal injury—exhibited only with fracture types that extend intra-articularly [ 8 ]. While there are various concomitant injuries, patients experiencing more than one concurrent injury with tibial tubercle avulsion fracture have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%